Selecting spare parts suitable for additive manufacturing: a design science approach - Chaudhuri, Atanu; Gerlich, Hasse Andreas; Jayaram, Jayanth; Ghadge, Abhijeet; Shack, Johan; Brix, Benjamin Hvidberg; Hoffbeck, Lau Holst; Ulriksen, Nikolaj (Taylor & Francis, 2020)
Additive manufacturing (AM) can help to deliver spare parts within short lead times and thus avoid maintaining huge inventories. Companies exploring opportunities to produce spare parts using AM face challenges in identifying suitable spare parts to be produced. Moreover, a single method may not be applicable for all companies and needs to be adapted considering the characteristics of the parts in the portfolio. This study follows a design science approach to addresses an evident research gap by developing a process to identify spare parts suitable for AM. The case data was analyzed using multi-criteria decision-making and cluster analysis techniques. The research contributes by developing and demonstrating a methodology to identify spare parts suitable for AM from a portfolio of a large number of spare parts, where adequate discrimination was not obtained by ranking all parts together. The study develops generic guidelines for spare parts selection for AM and outline the generalizability of the proposed methodology beyond the domain of part selection for AM.
Keywords: Design science; Cluster analysis; Multi-criteria decision-making; Spare parts selection; 3D Printing; Additive manufacturing